Penerapan Pembiasaan Literasi Budaya dan Kewargaan di SD Lab School FIP UMJ - Azmi Al Bahij; Devi Safitri; Esti Nur Alfadilla; Mechi Karima Kasipahu; Muhammad Nur Rizal; Ratna Wulan Sari; Rima Putri Mentari (Pusat Riset dan Inovasi Nasional, 2024)
Literacy is a complex skill possessed by an individual to utilize potential and abilities in processing and understanding information through activities such as reading, writing, speaking, calculating, and problem-solving. With literacy skills, one can apply their knowledge and experiences as references for the future. As responsible citizens, the skills of cultural and citizenship literacy become crucial aspects that must be mastered by elementary school students. This is considering the students' character in discerning and selecting the noble cultural values of the nation as a basis for their attitudes, actions, and behaviors amidst the diversity of society, nation, and state. This research was conducted at SD Lab School FIP UMJ using the SWOT analysis method. The research results indicate that cultural and citizenship literacy has been implemented at SD Lab School FIP UMJ and plays a significant role in enhancing the cultural and citizenship values of students.